Comparative Analysis of Hypertension Guidelines: Unveiling Consensus and Discrepancies in Lifestyle Modifications for Blood Pressure Control - Yi Wang; Yanxiang Liu; Lu Liu; Liqiong Hong; Huimin Chen (Cardiology Research and Practice)
Background. Hypertension is a major global health concern, and lifestyle modifications have been recommended as first-line treatment for hypertension in many guidelines. However, different guidelines may recommend different types of lifestyle adjustment, and it is unclear which ones are most effective. In this review, we compared hypertension guidelines to identify any differences and/or consensus in content, efficacy, and timing of initiation of lifestyle modifications. Methods. We conducted a search of databases to identify hypertension guidelines available in English. We extracted and compared information about lifestyle modifications recommended by the guidelines. Results. Five hypertension guidelines from America, Europe, the UK, Canada, and the International Society of Hypertension are included. They all recommend diet adaptation, sodium reduction, alcohol restriction, physical exercise, and weight reduction. Other lifestyle interventions emphasized by some guidelines, such as potassium supplementation, smoking cessation, and stress management, are not recommended by all the five guidelines. Among lifestyle changes, the dietary approaches to stop hypertension (DASH) diet may be considered the most effective treatment for reducing blood pressure. These guidelines recommend that for patients with high-normal blood pressure or grade 1 hypertension without high risk factors, lifestyle medicine should be used first for 3–6 months, if blood pressure is still not controlled, then start medication. For those patients who need drug treatment, lifestyle changes can also enhance the effects of antihypertensive therapy. Conclusion. Lifestyle modifications are crucial in the treatment of hypertension and should be recommended to most hypertensive patients. Among these lifestyle interventions, diet adaptation containing low sodium and alcohol restriction may be the most effective in reducing blood pressure. Physical exercise and weight reduction are also recommended. In some cases, lifestyle modifications should be tried first. They may also enhance the effects of antihypertensive drugs in other patients.